The Menorah and the seven-branched candelabrum: Jewish and Christian manifestations in the medieval and early modern periods - Worm, Andrea; Streicher, Maria (Andere Ästhetik – Studien, 2025)
For both Judaism and Christianity, the Menorah is an iconic artefact. It played a crucial role as an implement of the Tabernacle in the desert and the Temple in Jerusalem. After the destruction of the Temple and the eventual loss of the Menorah, it became the quintessential symbol of the Jewish people. It also figures prominently in Christian thought and imagery. Especially Christian monumental seven-branched candelabra raise questions about their spatial aesthetics as well as their liturgical and performative functions. This volume offers interdisciplinary reflections on the Menorah in both Jewish and Christian traditions, and thus contributes not only to a better understanding of their cultural entanglement in pre-modern times, but also to a more differentiated view of their specific and contextualaesthetic qualities